The Jews of Moscow, Kiev and Minsk : identity, antisemitism, emigration - Brym, Robert J. (Macmillan, 1994)
The Jews of the former Soviet Union have always been the subject of intense controversy. In the past 25 years, especially, they have been the source of considerable speculation. How many of them are there? How strongly do they identify themselves as Jews? How do they perceive antisemitism in their countries? Will they leave or will they stay? If they leave, where will they go? The issues swirling around the Jews in the republics now known as the Commonwealth of Independent States (CIS) have sparked debate because the status of these Jews has deep policy implications for Russia, Israel, the United States, and other countries. Too little fact has informed this debate, and even less theory. Until very recently, surveys of the actual intentions, perceptions, motivations, and fears of Jews in the region were out of the question. For obvious reasons, this has all changed. This volume is the first based on an on-site survey of Jews in the CIS. In addition to providing data on the Jews of Moscow, Kiev, and Minsk - who collectively account for over a quarter of all Jews residing in the three Slavic republics of the CIS - the author places the survey results in their social and historical contexts. He explains why ethnic distinctiveness persisted and even became accentuated in the Soviet era and also describes the position of Jews in Soviet and post-Soviet society and some of the dilemmas they face. This book will be crucial reading for anyone interested not only in the general situation of the Jews of the former Soviet Union but in their actual perceptions, worldviews, and plans for the future.